Local SIP Overload Control - Luca De Cicco; Giuseppe Cofano; Saverio Mascolo (Wired/Wireless Internet Communication, 2013)
The Session Initiation Protocol (SIP) is a signaling framework that allows two or more parties to establish, alter, and terminate various types of media sessions. The mechanism employed by the standard SIP is not effective in handling overload situations that occur when the incoming flow of requests overcomes the processing resources of the server. In this paper we present a local overload control system based on feedback control theory. The algorithm has been implemented in Kamailio (OpenSER) and a performance comparison with Ohta and Occupancy (OCC) overload control algorithms has been performed. The proposed control system efficiently counteracts overload situations providing a goodput which is close to the optimal while maintaining low call establishment delays and retransmission ratios. On the other hand, Ohta and OCC algorithms provide higher call establishment delays and retransmission ratio and lower goodputs.